Performance enhancement of a solar powered air conditioning system using passive techniques and SWCNT /R-407c nano refrigerant. (December 2019) - Rahman, Shek; Issa, Salah; Said, Zafar; El Haj Assad, Mamdouh; Zadeh, Rashed; Barani, Yazan
Abstract: This work presents a novel solar powered air-conditioning system that operates under UAE climate conditions. Distinct passive techniques and refrigerant-based nanofluids, termed as ''Nano refrigerants'' were investigated to enhance the system performance. Results suggest that the proposed design of using passive techniques such as: roofing reflective material, trees, double-glazed windows, and overhang, reduces the space cooling load by 31.5%. Nano refrigerants effect on the coefficient of performance (COP) resulted in improving COP by adding of 5 vol % single wall carbon nanotube (SWCNT) into R407c refrigerant at temperatures of 283–308 (K). The results indicate that the thermal conductivity of SWCNT/R-407c nano refrigerant increased by about 15.6% compared to the base refrigerant (R-407c) at 305 K. The usage of nano refrigerant reduces consumption of compressor work by 4%. Furthermore, SWCNT/R-407c nanorefrigerant shows the notable improvement of COP of at about 17.02% for thermal conductivity and at about 10.06% for specific heat, respectively compared to R-407c refrigerant. Finally, comparisons between the proposed design and the conventional system as well as with previous literature. Results demonstrate that the proposed system reduces the compressor work by 34% and the COP is increased by 4.59% compared to the conventional air-conditioning system.